(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Betulinic acid (BA) is a lupane-type triterpene that has been identified and isolated from various plant species used in ethnomedicine in various cultures across the world. This study was undertaken to elucidate the mechanisms underlying the anti-ulcer effect of Betulinic acid. The effect of BA on indomethacin-induced ulcer, gastric mucus secretion, gastric mucus cells count, basal and histamine-induced gastric acid secretion and levels of malondialdehyde formation were studied using dose of 0.5, 1.5, and 3.0 mg/kg. The results showed that BA reduced indomethacin-induced ulceration significantly and significantly increased (p < 0.05) gastric mucus secretion in the 1.5 mg/kg and 3.0 mg/kg BA treated rats compared to the control rats. There was a significant increase (p < 0.05) in the mucus cells count in all the treated groups which is in a dose- dependent manner compared to the control group. There was significant decrease (p < 0.05) in gastric acid secretion in each of the BA treated groups compared to the control. Malondialdehyde concentration significantly decrease (P < 0.05) in all the treated groups compared to the control. The anti-gastric ulcer effect of BA may be mediated via decreasing gastric acid secretion, increasing gastric mucus secretions, increasing the number of gastric mucus cells and also by reducing the level of MDA concentration.